Physical and biological controls on DMS, P dynamics in ice shelf‐influenced fast ice during a winter‐spring and a spring‐summer transitions. Issue 5 (14th May 2014) - Carnat, Gauthier; Zhou, Jiayun; Papakyriakou, Tim; Delille, Bruno; Goossens, Thomas; Haskell, Tim; Schoemann, Véronique; Fripiat, François; Rintala, Janne‐Markus; Tison, Jean‐Louis
Abstract We report the seasonal and vertical variations of dimethylsulfide (DMS) and its precursor dimethylsulfoniopropionate (DMSP) in fast ice at Cape Evans, McMurdo Sound (Antarctica) during the spring‐summer transition in 2011 and winter‐spring transition in 2012. We compare the variations of DMS, P observed to the seasonal evolution of the ice algal biomass and of the physical properties of the ice cover, with emphasis on the ice texture and brine dynamics. Isolated DMS and DMSP maxima were found during both seasonal episodes in interior ice and corresponded to the occurrence of platelet crystals in the ice texture. We show that platelet crystals formation corresponded in time and depth to the incorporation of dinoflagellates (strong DMSP producers) in the ice cover. We also show that platelet crystals could modify the environmental stresses on algal cells and perturb the vertical redistribution of DMS, P concentrations. We show that during the winter‐spring transition in 2012, the DMS, P profiles were strongly influenced by the development and decline of a diatom‐dominated bloom in the bottom ice, with DMSP variations remarkably following chl a variations. During the spring‐summer transition in 2011, the increase in brine volume fraction (influencing ice permeability) on warming was shown to trigger (1) an important release of DMS to the under‐ice water through brine convection and (2) a vertical redistribution of DMSP across the ice.